Insight into the structure of decagonite – the extraterrestrial decagonal quasicrystal - Buganski, Ireneusz (IUCrJ, 2021)
A set of X-ray data collected on a fragment of decagonite, Al(71)Ni(24)Fe(5), the only known natural decagonal quasicrystal found in a meteorite formed at the beginning of the Solar System, allowed us to determine the first structural model for a natural quasicrystal. It is a two-layer structure with decagonal columnar clusters arranged according to the pentagonal Penrose tiling. The structural model showed peculiarities and slight differences with respect to those obtained for other synthetic decagonal quasicrystals. Interestingly, decagonite is found to exhibit low linear phason strain and a high degree of perfection despite the fact it was formed under conditions very far from those used in the laboratory.